The Effect of Health Education on Covid-19 on the Anxiety Level of the “Healthy People” Group in Seretan Village, North Sulawesi - Syenshie Virgini Wetik; Grace Benedikta Polii (Jurnal Kesehatan, 2021)
Anxiety is a psychological response felt by most people as a result of the COVID-19 pandemic. This is due to the lack of information about COVID-19 and how to deal with the anxiety they feel. This study aims to determine the effect of providing health education about covid-19 on the level of public anxiety. The method used was quasi-experimental pre-post-test design with control group. The sampling technique was purposive sampling with inclusion and exclusion criteria and a sample of 32 respondents was obtained. The research used the Hamilton Anxiety Rating Scale (HARS) questionnaire. The analysis of the data used paired t-test and independent t-test. The results showed that the p-value < 0.05 which means that there was a significant increase in the level of public anxiety in the intervention and control groups before and after the intervention in the form of health education was given. there is a significant difference in anxiety level at the intervention and control group after the health education intervention. The results of this study can be used as a scientific basis to increase educational activities for the community about COVID-19 such as health workers, health agencies and institutions, especially those related to education on mental/psychological health problems.